Avaliação dos resultados da psicoterapia psicanalítica com crianças - Deakin, Elisabeth Kuhn (Pontifícia Universidade Católica do Rio Grande do Sul, 2013)
Made available in DSpace on 2013-08-07T19:08:15Z (GMT). No. of bitstreams: 1 000403295-Texto+Completo-0.pdf: 811477 bytes, checksum: 9c353e7a8f09a44da384610e40b00353 (MD5) Previous issue date: 2008 === This dissertation aimed to review the current research in child psychotherapy, more specifically, the child psychoanalytic psychotherapy, as well as to investigate the effectiveness of child psychoanalytic psychotherapy and early termination of this treatment modality. Three different studies were carried out. The first was a theoretical study which discussed two models that are mostly used to evaluate psychotherapy outcome: the efficacy model and the effectiveness model. The second study was an empirical research on individual child psychoanalytic psychotherapy outcome in a clinical outpatient setting in Porto Alegre, Brazil. Three psychological testing (Rorschach, Bender, WISC III) were administered in 23 children, ages 6 to 11 years old and the Child Behavior Check List (CBCL) was completed by the parents. All testing was completed before the beginning of the psychoanalytic psychotherapy. The same measures were repeated after 12 months of intervention. The 23 children who received individual psychoanalytic psychotherapy were compared with 22 children (same age, gender and total CBCL score) who did not receive any kind of intervention. In the clinical group the results indicated statistical significant reduction of anxiety symptoms (. 002) and school problems (. 031) , improvement in interpersonal relationships (. 022) and positive change in the following CBCL scales : withdrawn (. 010), thought processing (. 022), anxiety and depression (. 017), internalizing (. 008) and total (. 003) . An effect size of 0,696 was calculated based on the CBCL total scale before and after intervention . No statistical significant differences were found in the WISC III and Bender-Gestalt results.The third study comprised an empirical research in child psychotherapy drop out in which 24 children who completed 12 months of psychoanalytical psychotherapy were compared with 38 children who dropped out of psychotherapy before 12 months of intervention. Statistical significant differences were found in the following variables: gender, presenting problems, frequency of sessions, child’s impulse and emotion control and the socialization, somatic, anxiety, depression, internalizing CBCL scales. The results revealed that the child psychoanalytical psychotherapy is mostly effective in the treatment of female children, who present internalizing problems, such as anxiety and depression, has little control of impulses and emotions and attends at least 12 months of psychoanalytical psychotherapy twice weekly. === Esta tese objetivou fazer uma revisão sobre a pesquisa em psicoterapia com crianças, mas especificamente a psicoterapia psicanalítica, bem como investigar a efetividade e o abandono prematuro desta modalidade de atendimento. Para tanto foram elaborados três estudos. O primeiro é um trabalho de revisão sobre os modelos de investigação mais utilizados na atualidade para avaliar resultados de psicoterapia: o modelo de estudo de eficácia e o modelo de estudo de efetividade. O segundo é uma pesquisa empírica sobre os resultados da psicoterapia psicanalítica individual com crianças em um ambulatório de Porto Alegre, RS. Neste estudo foram aplicados três testes psicológicos com 23 crianças de 6 a 11 anos (WISC III, Bender-Gestáltico e Rorschach) e um questionário auto-administrado (CBCL) com os pais ou responsáveis. Todos os testes foram aplicados antes da intervenção psicoterápica psicanalítica e, novamente, após 12 meses da primeira avaliação seguindo os mesmos princípios metodológicos. As 23 crianças que receberam atendimento psicoterápico psicanalítico foram comparadas com 22 crianças do mesmo sexo, idade e resultado total do CBCL que não receberam tratamento. Neste estudo, foram encontradas diferenças positivas estatisticamente significantes no grupo clínico que recebeu intervenção psicoterápica nas seguintes variáveis: redução dos sintomas de ansiedade (. 002) e problemas escolares (. 031); melhora das relações interpessoais medidas pelo Rorschach (. 022); melhora nas escalas de retraimento (. 010), pensamento(. 022), ansiedade e depressão (. 017), introversão (. 008) e total (. 003) medidas pelo CBCL. O resultado da escala total do CBCL foi utilizado para cálculo do tamanho de efeito da intervenção, que foi estimado em 0. 696, portanto, moderado.Não foram encontradas diferenças estatisticamente significantes nos testes do WISC III e Bender. Por último foi realizada uma pesquisa empírica sobre abandono de psicoterapia com crianças no qual foi feita uma comparação de uma amostra de 24 crianças que completaram 12 meses de psicoterapia psicanalítica com uma amostra de 38 crianças que interromperam prematuramente o tratamento. Foram encontradas diferenças estatisticamente significantes nas variáveis sexo, sintomas, freqüência dos atendimentos, capacidade da criança de controlar as emoções (%CF) e de controlar impulsos (%m + mF), medidas pelo Rorschach e escalas de sociabilidade, queixas somáticas, ansiedade e depressão e comportamentos internalizantes medidas pelo CBCL. Este estudo revelou que a psicoterapia psicanalítica é efetiva no tratamento da criança do sexo feminino, que apresenta transtornos internalizantes, tem maior descontrole de emoções e impulsos e recebe atendimento com uma freqüência de duas vezes por semana por pelo menos 12 meses.